Nitrogen, Phosphorus, and Potassium Fertilization for Newly Established Tall Fescue - D. W. Sweeney; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2016)
(Abstract only. Link to: http://newprairiepress.org/kaesrr/vol1/iss4/1/) Article is nearly identical toNitrogen, Phosphorus, and Potassium Fertilization for Newly Established Tall Fescuepreviously published in Southeast Agricultural Research Center 2015, included in this PDF. First-year production of tall fescue (Site 1 in 2013 and Site 2 in 2014) was affected by nitrogen (N) and phosphorus (P), but not potassium (K) fertilization. Environmental conditions likely influenced the growth of the fescue and the response to fertilizer N and P in the first year of production at the two sites.
Keywords: Nitrogen; Phosphorus; Potassium; Fescue